Nilai Religius dalam Buku Teks Bahasa Indonesia SMP Kurikulum 2013 - Nur Indah Sholikhati (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2020)
Textbooks are one important component in the learning process. It is hoped that Indonesian textbooks will not only have linguistics and literature, but there will also be the inculcation of the values of character education. This study aims to describe the cultivation of religious character education in Indonesian Language textbooks at SMP Curriculum 2013. The research conducted was a descriptive qualitative study. The data in this study are in the form of phrases, words, clauses, sentences, paragraphs and discourses that contain content about inculcation of character education in Indonesian textbooks for SMP Curriculum 2013. In this study, the data were obtained from Indonesian textbooks Class VII, VIII, and IX Curriculum 2013. In this study, the research instrument is a researcher who is equipped with theories about character education. In addition, researchers are equipped with instruments in the form of data cards containing religious character education. The instrument was validated by content validation by experts (expert judgment) conducted by language teaching experts. The validity of the data is done by peer examination techniques through discussion or Focus Group Discussion (FGD). Data analysis in this study uses an interactive analysis model.